Prevalence of disability in a composite ≥75 year-old population in Spain: A screening survey based on the International Classification of Functioning - Virués-Ortega, Javier; de Pedro-Cuesta, Jesús; Seijo-Martínez, Manuel; Saz, Pedro; Sánchez-Sánchez, Fernando; Rojo-Pérez, Fermina; Rodríguez, Fernanda; Mateos, Raimundo; Martínez-Martín, Pablo; Mahillo, Ignacio; Gascon-Bayarri, Jordi; Garre-Olmo, Josep; et al. (BMC public health, 2011)
Background The prevalence and predictors of functional status and disability of elderly people have been studied in several European countries including Spain. However, there has been no population-based study incorporating the International Classification of Functioning, Disability and Health (ICF) framework as the basis for assessing disability. The present study reports prevalence rates for mild, moderate, and severe/extreme disability by the domains of activities and participation of the ICF. Methods Nine populations surveyed in previous prevalence studies contributed probabilistic and geographically defined samples in June 2005. The study sample was composed of 503 subjects aged ≥75 years. We implemented a two-phase screening design using the MMSE and the World Health Organization-Disability Assessment Schedule 2 nd edition (WHO-DAS II, 12 items) as cognitive and disability screening tools, respectively. Participants scoring within the positive range of the disability screening were administered the full WHO-DAS II (36 items; score range: 0-100) assessing the following areas: Understanding and communication, Getting along with people, Life activities, Getting around, Participation in society, and Self-care. Each disability area assessed by WHO-DAS II (36 items) was reported according to the ICF severity ranges (No problem, 0-4; Mild disability, 5-24; Moderate disability, 25-49; Severe/Extreme disability, 50-100). Results The age-adjusted disability prevalence figures were: 39.17 ± 2.18%, 15.31 ± 1.61%, and 10.14 ± 1.35% for mild, moderate, and severe/extreme disability, respectively. Severe and extreme disability prevalence in mobility and life activities was three times higher than the average, and highest among women. Sex variations were minimal, although life activities for women of 85 years and over had more severe/extreme disability as compared to men (OR = 5.15 95% CI 3.19-8.32). Conclusions Disability is highly prevalent among the Spanish elderly. Sex- and age-specific variations of disability are associated with particular disability domains.